A caracterização do documento jurídico para a organização da informação - Simone Torres de Souza (2013)
In establishing standards of conduct for society, Law makes use of complex processes that generate a large volume of documents. This sort of document, namely the legal document, is among the objects of study of Information Science. In the context of Information Science, we can find several reasons that justify the work we develop here: the importance of legal documentation for the law and for society as a whole, the smallnumber of Information Science studies about legal documentation, the large volume of information produced in Law and the large number of Library and Information Science professionals working in the legal segment. We present as our research issue the search for ways of identifying the features of a legal document. Our first hypothesis is thatavailable Information Science approaches to legal documentation are not able to clearly define legal documents or identify all their main features. Our second hypothesis is that, in addition to Information Science approaches, one should use theoretical contributions of Philosophy of Language, Law and Archival studies in order to properly characterizethe legal document. Our main goal here is to make up with a theoretical model that defines the legal document, as well as lists the elements one have to found in a document in order to characterize it as a legal document. To do so, we make use of theoretical studies carried out in Information Science, Law, Philosophy of Language and Archival Studies. Moreover, we enumerate the characteristics of legal documents andtest the adequacy of the proposed criteria for specific cases. In order to reach our goals we use the hypothetical-deductive method. Besides, the kind of research we propose can be considered as applied research, regarding its nature; as qualitative research, regarding the way the problem is approached; as exploratory research, regarding its goals; documentary research and literature review, regarding its technical procedures. As result of the literature review, we propose our theoretical model composed of three main parts: a well-founded definition for legal documents, a set of six categories in which such definition is unfolded (including the respective characteristics) and a glossary of legal documentary species. As a result of documentary research, we analyse a sample composed of fifteen selected documents, which are representative of all categories present in the proposed theoretical model. We found that our hypotheses were confirmed. Thus, we were able to formulate a general definition for legal documents unfolded into six categories, which are established according to their purpose, content,format and context of creation. Finally, we concluded that our goals were achieved.